2022
DOI: 10.1123/jsr.2021-0191
|View full text |Cite
|
Sign up to set email alerts
|

Lower Quadrant Swing Biomechanics Identifies Golfers With Increased Risk of Low Back Pain: A Prospective Longitudinal Cohort Study

Abstract: Context: Elite golfers have a high incidence of low back pain. Recent reviews have emphasized the need for investigation into how to prevent low back pain in golfers, prompting the current study. Design: Prospective longitudinal cohort study. Methods: Forty-one injury-free golfers were included in this study. At baseline, lower quadrant joint angles and club and ball performance were measured while each golfer performed 10 drives. The golfers were then monitored for 6 months and were allocated into 2 groups de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Data from 10,437 subjects were extracted across the 58 studies included in this systematic review (1)(2)(3)(4)11,12,14,19,20,(23)(24)(25)(26)28,(30)(31)(32)(33)(35)(36)(37)(38)(39)(40)(41)(42)(43)(45)(46)(47)(48)(49)(50)(51)(52)54,56,59,(62)(63)(64)(65)(66)(68)(69)(70)(71)(72)(73)(76)(77)(78)…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from 10,437 subjects were extracted across the 58 studies included in this systematic review (1)(2)(3)(4)11,12,14,19,20,(23)(24)(25)(26)28,(30)(31)(32)(33)(35)(36)(37)(38)(39)(40)(41)(42)(43)(45)(46)(47)(48)(49)(50)(51)(52)54,56,59,(62)(63)(64)(65)(66)(68)(69)(70)(71)(72)(73)(76)(77)(78)…”
Section: Subjectsmentioning
confidence: 99%
“…x em Self-perception of being overweight (62) x r Golf play per week (25,26,62,71,79) ? r ↑↑ se Golf practice per week (25,40,62,68,69) ? r o em o r Golf rounds per week or month (42,(68)(69)(70) o em Full-swing practice sessions per month (42) ↑↑↑ em Balls struck per full-swing practice sessions (42) o em Range practice per week (70) ↓↓ em Putting sessions per week or month (42,(68)(69)(70) o em Time spent per putting sessions (42) o em Short game practice per week (70) x em Warm-up before play or practice (26,28,50,71) o r Resistance training per week (68)(69)(70) x em Cardiovascular training per week (68)(69)(70) x em Mobility or flexibility training per week (68)(69)(70) x em Postural training per week (68)(69)(70) o em Carrying golf bag (50) o r Accuracy from tee to green (% in regulation) (32) x e Golf club changes (50) o r Golf club shafts used (50)…”
Section: Physical Risk Factors For Musculoskeletal Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…During the golf setup, flaring the lead foot to externally rotate the lower limb at setup may provide a golfer with increased allowance for hip IR throughout the swing, naturally decreasing forces through, and injury risk to, the lumbar spine. In addition, there is evidence that increased trail hip adduction at the top of the backswing (correlating with the common golf fault of “swaying”) is correlated with increased risk of LBP (27).…”
Section: Spinementioning
confidence: 99%
“…Those with decreased ankle ROM and stability may tend to place increased stresses on other joints as previously detailed. For example, a 2022 study by Quinn et al (27) found that golfers with less dorsiflexion in the lead ankle at the top of the backswing are more likely to develop LBP. As emphasized throughout this review, many swing faults, biomechanical compensations, and injuries may be a result of deficiencies more proximal in the kinetic chain.…”
Section: Upper Limbmentioning
confidence: 99%